Exercise training at high altitude: How do the respiratory muscles respond? - LaStayo, Paul C.; Lindstedt, Stan L. (Acta Andina, 2025)
Like all vertebrate skeletal muscles, the ventilatory muscles (VM) of humans can adaptively improve in their functional capacities Since these changes occur consistently in response to specific VM strenght and endurance training protocols, one would assume the same principles of skeletal muscle training can be applied to the VM. It is apparent, however, that VM adaptations require a very strong exercise stimulus (and perhaps a VM training specific stimulus) as chronic whole animal endurance exercise do not appear to have significant or even predictable effect effect on the structural or functional aspects of the VM This manuscript reviews the equivocal results regarding animals respiratory muscles to various programs of regular endurance exercise. It also reviews endurance training studies at high altitude, predicted to increase the strenght of the stimulas for VM adaptations, which again fails to elicit VM functional changes. Finally, since there seems to be a poor relationship between VM power and endurance with increases in (even al altitude) the question is raised as to wheter the evolutionary design of the VM is primarily for "breathing". We propose an alternative hypothesis that ventilation has not been selected as the primary task of the VM, Rather, non-breathing tasks put a larger demand on the "ventilatory muscles" than does ventilation per se.